Spatial differentiation and influencing factors of rural-area multi-functionality in Hebei province based on a spatial econometric model - Ma, Lijun; Xu, Shuang; Guo, Fengyu; Xu, Lei; Yin, Shi (Frontiers in Environmental Science, 2022)
The main objectives of the study are to establish a rural-area multi-functionality evaluation index system, reveal the characteristics and identify influencing factors of rural-area multi-functionality differentiation in Hebei Province. A back-propagation neural network model and a spatial econometric model were used in the study. The results of this study as follows. The spatial differentiation of rural-area multi-functionality shows the opposite distribution to that of the agricultural production and economic development functions. The distribution of the socio-cultural function was found to be opposite to that of the ecological function, while the distribution of the socio-cultural function was found to be similar to that of the economic development function. There was a positive spatial correlation between rural functional patterns. The difference in rural-area multi-functionality development conditions was found to be the main reason for agglomeration distribution differences. The agricultural production function is mainly affected by agricultural, ecological, and industrial conditions. The function of economic development was found to be mainly affected by population and traffic conditions. The socio-cultural functions were found to be mainly affected by population and economic conditions. The ecological function was greatly affected by agricultural, population, and ecological conditions. This study provides further insights into the functions of rural regions and enriches the theories used in rural regional studies by closely analyzing the causes of the generation of and changes in rural-area multi-functionality. In the future, the government department should strengthen the construction of transportation, agricultural infrastructure, and industrial infrastructure.